2009
DOI: 10.1111/j.1467-9914.2008.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Training, Job Satisfaction, and Workplace Performance in Britain: Evidence from WERS 2004

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 56 publications
8
118
0
8
Order By: Relevance
“…Training programmes are found to have a modest or no effect on unemployment exit rates (Gerfin and Lechner, 2002;Andrén and Andrén, 2006;Crépon et al, 2007;Lechner et al, 2008;Lalive et al, 2008;Sianesi, 2008) and on wages (Heckman et al, 1999). Positive effects are instead found on the future employment stability (Crépon et al, 2007;Lechner et al, 2008) and Jones et al (2009) show that training is significantly and positively associated with job satisfaction.…”
Section: Introductionmentioning
confidence: 94%
“…Training programmes are found to have a modest or no effect on unemployment exit rates (Gerfin and Lechner, 2002;Andrén and Andrén, 2006;Crépon et al, 2007;Lechner et al, 2008;Lalive et al, 2008;Sianesi, 2008) and on wages (Heckman et al, 1999). Positive effects are instead found on the future employment stability (Crépon et al, 2007;Lechner et al, 2008) and Jones et al (2009) show that training is significantly and positively associated with job satisfaction.…”
Section: Introductionmentioning
confidence: 94%
“…Implicit in these definitions is the importance of both internal and external factors as determinants of job satisfaction. Relevant research has demonstrated the importance of job satisfaction in organizations, especially in terms of efficiency, productivity, employee relations and absenteeism (Dormann and Zapf 2001;Gyekye and Salminen 2006;Jones, Jones, Latreille and Sloane 2009).…”
Section: Job Satisfaction and Absenteeismmentioning
confidence: 99%
“…Yet, as shown by Zwick (2006) for the German case, on-the-job training enhances rm productivity. Moreover, employees receiving training are also more satis ed with their job and, therefore, have a higher job performance (Jones et al, 2009). Regarding the relationship of xed-term employment and the incentive to invest in human capital, an increasing share of employees with temporary contracts reduces labor productivity due to lower investments in rm speci c human capital.…”
Section: Temporary Employment and Human Capitalmentioning
confidence: 99%